Resistance Training in Spontaneously Hypertensive Rats with Severe Hypertension - Rodrigo Vanerson Passos Neves (Arquivos Brasileiros de Cardiologia, 2016)
Abstract Background: Resistance training (RT) has been recommended as a non-pharmacological treatment for moderate hypertension. In spite of the important role of exercise intensity on training prescription, there is still no data regarding the effects of RT intensity on severe hypertension (SH). Objective: This study examined the effects of two RT protocols (vertical ladder climbing), performed at different overloads of maximal weight carried (MWC), on blood pressure (BP) and muscle strength of spontaneously hypertensive rats (SHR) with SH. Methods: Fifteen male SHR ENT#091;206 ± 10 mmHg of systolic BP (SBP)ENT#093; and five Wistar Kyoto rats (WKY; 119 ± 10 mmHg of SBP) were divided into 4 groups: sedentary (SED-WKY) and SHR (SED-SHR); RT1-SHR training relative to body weight (~40% of MWC); and RT2-SHR training relative to MWC test (~70% of MWC). Systolic BP and heart rate (HR) were measured weekly using the tail-cuff method. The progression of muscle strength was determined once every fifteen days. The RT consisted of 3 weekly sessions on non-consecutive days for 12-weeks. Results: Both RT protocols prevented the increase in SBP (delta - 5 and -7 mmHg, respectively; p > 0.05), whereas SBP of the SED-SHR group increased by 19 mmHg (p < 0.05). There was a decrease in HR only for the RT1 group (p < 0.05). There was a higher increase in strength in the RT2 (140%; p < 0.05) group as compared with RT1 (11%; p > 0.05). Conclusions: Our data indicated that both RT protocols were effective in preventing chronic elevation of SBP in SH. Additionally, a higher RT overload induced a greater increase in muscle strength.